2023
DOI: 10.3390/mi14020346
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Nanoscale Vacuum Channel Triodes Based on the Material System of Vacuum Electronics

Abstract: Nanoscale vacuum channel triodes realize the vacuum-like transmission of electrons in the atmosphere because the transmission distance is less than the mean free path of electrons in air. This new hybrid device is the deep integration of vacuum electronics technology, micro-nano electronics technology, and optoelectronic technology. It has the advantages of both vacuum and solid-state devices and is considered to be the next generation of vacuum electronic devices. In this work, vertical nanoscale vacuum chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The analysis also showed that in the case of the FIB microtriodes, The local electric field strength near the cathode can be estimated using Equation (2), where the electric field strength is the product of the applied voltage and the field enhancement factor. The latter is inversely proportional to the slope according to Equation (5). The Fowler-Nordheim plots in Figures 7b and 9b show that the slope for the PL microtriode and the FIB microtriode was 300.2 and 26.3, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The analysis also showed that in the case of the FIB microtriodes, The local electric field strength near the cathode can be estimated using Equation (2), where the electric field strength is the product of the applied voltage and the field enhancement factor. The latter is inversely proportional to the slope according to Equation (5). The Fowler-Nordheim plots in Figures 7b and 9b show that the slope for the PL microtriode and the FIB microtriode was 300.2 and 26.3, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Advances in micro-and nanotechnology have led to a renewed interest in vacuum electronics [1][2][3][4][5]. Vacuum electronic devices have several advantages over semiconductor devices, making them the preferred choice for some applications.…”
Section: Introductionmentioning
confidence: 99%
“…When a uniform AC field in the kHz frequency range is applied to a metallodielectric Janus particle within a liquid, the particle reorients such that the interface between the hemispheres aligns parallel with the field due to dielectrophoresis (DEP), yielding the greatest possible induced dipole moment. 46,47 After this reorientation, ions in solution accumulate preferentially at the surface of the metallic hemisphere, generating an induced charge cloud. At steady state, due to this induced charge cloud, fluid is drawn to the particle parallel to the field and ejected perpendicular to the field, away from the two hemispheres.…”
Section: Resultsmentioning
confidence: 99%